Kaji Eksperimental Solar Chimney Power Plant (SCPP) Dengan Concentrating Lens Yang Disusun Dengan Pola Zigzag - Dandi, Erico; Kurniawan, Iwan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Chimney Solar Power Plant (SCPP) is part of a form of solar thermal collector technology. SCPP has the working principle of absorbing solar thermal energy using a glass collector, then converting the hot air that flows into electrical energy through a turbine. Converging lenses can increase the output power. The function of the focusing lens can increase the intensity of light that will be received by the receiver so that the light beam received is greater than without a converging lens. This tool consists of 4 main components, namely: cover, collector, buffer and condensing lens. The support is made of reinforcing steel which is formed into a circle. The collector is made of concrete and painted black to absorb more heat and is circled. The collector is installed under the support and then a cover made of clear plastic is attached. At the top of the collector, a concentrate lens is installed. This study aims to determine the temperature increase that occurs in the solar collector using a concentrated lens and to determine the potential of the solar collector using a concentrated lens and without using a concentrated lens. The results of tests carried out on solar collectors show that solar collectors built without concentrating lenses can increase the air temperature and also increase the incoming air flow. The addition of a concentrated lens with a zigzag pattern gives the effect of increasing the temperature on the solar collector. So that through solar radiation, concentrated lenses can also improve the performance of solar collectors. The average wind power generated by a system without a concentration lens is 0.5W, with 21 concentrating lenses at 1.38W, and with 36 concentrating lenses at 1.56W. Keywords: SCPP, zigzag, concentrating lens, radiation, collector